Clinically unapparent infantile thiamin deficiency in Vientiane, Laos - Khounnorath, S; Chamberlain, K; Taylor, A; Soukaloun, D; Mayxay, M; Lee, S; Phengdy, B; Luangxay, K; Sisouk, K; Soumphonphakdy, B; Latsavong, K; Akkhavong, K; et al. (Public Library of Science, 2011)
Background Beriberi occurs in Vientiane, Lao PDR, among breastfed infants. Clinical disease may be the tip of an iceberg with subclinical thiamin deficiency contributing to other illnesses. Thiamin treatment could improve outcome. Methodology/Principal Findings A cohort of 778 sick infants admitted during one year without clinical evidence of beriberi were studied prospectively and erythrocyte transketolase assays (ETK) performed. Biochemical thiamin deficiency was defined both in terms of the activation coefficient (α>31%) and basal ETK activity <0.59 micromoles/min/gHb. Of the 778 infants, median (range) age was 5 (0–12) months, 79.2% were breastfed, 5.1% had α>31% and 13.4 % basal ETK<0.59 micromoles/min/gHb. Infants ≥2 months old had a higher frequency of biochemical markers of thiamin deficiency. Mortality was 5.5% but, among infants ≥2 months old, mortality was higher in those with basal ETK<0.59 micromoles/min/gHb (3/47, 6.4%) than in those with basal ETK≥0.59 micromoles/min/gHb (1/146, 0.7%) (P = 0.045, relative risk = 9.32 (95%CI 0.99 to 87.5)). Multivariate regression analysis indicated that infant age ≥2 months and fewer maternal years of schooling were independently associated with infant basal ETK<0.59 micromoles/min/gHb. Conclusions/Significance Clinically unapparent thiamin deficiency is common among sick infants (≥2 months old) admitted to hospital in Vientiane. This may contribute to mortality and a low clinical threshold for providing thiamin to sick infants may be needed.